The Need for Gender-Responsive Policy During The COVID-19 Pandemic: A Literature Review - Fransiska Pangesti A; Nuzulul Kusuma Putri (Universitas Airlangga, 2022)
Background: Covid-19 has infected more than million of people globally. The Covid-19 pandemic has an impact in various aspects including gender. Pandemic Covid-19 are increasing the gender gap in terms of employment, income, and household responsibility. This provide that Covid-19 pandemic is not gender-neutral. Objectives: This study aims to identify the issues in promoting gender-responsive policy during the COVID-19 pandemic between women and men.Methods: This is a literature review of original articles discussing the need for gender-responsive policy during the COVID-19 pandemic. At least ten original articles obtained from Scholar Google were synthesized in this literature review.Discussion: Restrictions on mobility and activity during the pandemic have an impact on woman in social and economy term such as declining income, job loss, and increased burden of dual roles. The integration of gender mainstreaming can be a responsive way to overcome this problem. In this cases, several possible policies that will be evaluated predominantly are social protection for the community who identified as COVID-19 impacted and employee adjustment and well-being in the era of COVID-19 and post COVID-19.Conclusions: This detailed analysis of the intersection of these economic losses and gender-responsive policy are needed to correct the inequalities of economic productivity experienced by different sexes. The results of the analysis will help policymakers to be able to formulate what programs are gender-responsive in overcoming gender inequality during the pandemic.